Plasma asymmetric dimethylarginine predicts restenosis after coronary angioplasty - Derkacz, Arkadiusz (Termedia Publishing House, 2011)
INTRODUCTION: Asymmetric dimethylarginine (ADMA) is an endogenous competitive inhibitor of endothelial nitric oxide synthase. Asymmetric dimethylarginine may influence the process of restenosis after coronary angioplasty. The aim of the study was to determine if initial plasma ADMA level could predict restenosis after coronary angioplasty and stenting. MATERIAL AND METHODS: The study group consisted of 60 consecutive patients (10 women and 50 men, average age 58.9 ±10.4 years old), who underwent percutaneous coronary angioplasty with bare metal stenting for stable coronary artery disease. All patients underwent follow-up coronary angiography after a 6-month period. Patients were divided into two groups, one with restenosis (n = 22), and the other one without restenosis (n = 38). In addition to measuring acknowledged restenosis risk factors, plasma ADMA level was measured before initial angiography. RESULTS: Asymmetric dimethylarginine plasma level was significantly higher in the group with restenosis than in the group without restenosis (1.94 ±0.94 µmol/l vs. 0.96 ±0.67 µmol/l; p < 0.05). L-arginine/ADMA ratio was also decreased in the group with restenosis, when compared with the group without restenosis (p < 0.05). Multivariate logistic regression revealed that independent restenosis risk factors were characterised by an initially high ADMA level (p < 0.01), advanced age (p < 0.05) and low level of HDL cholesterol (p < 0.05). CONCLUSIONS: Pre-procedural elevated plasma ADMA level increases the risk of restenosis in patients who underwent coronary angioplasty and stenting with bare metal stents.